The concept model of sustainable buildings refurbishment - Mickaitytė, Aistė; Zavadskas, Edmundas K.; Kaklauskas, Artūras; Tupėnaitė, Laura (International Journal of Strategic Property Management, 2010)
Sustainable development principles reaching many spheres of human activities, public buildings refurbishment is not an exemption in this case. Buildings refurbishment supports excellent opportunities to reduce energy consumption in buildings as well as encourages other sustainable refurbishment principles implementation – citizens’ healthcare, environment protection, rational resources use, information about sustainable refurbishment dissemination and stakeholders groups’ awareness. During the pilot refurbishment FP‐6 project Brita in PuBs, authors of this article have developed conceptual sustainable public buildings refurbishment model. Model was created basing on sustainable development principles, their consideration in decision making process and model efficiency influencing factors. In order to demonstrate models’ application possibilities following the healthcare principle, practical case study of Vilnius Gediminas Technical University main building pollution mapping is given at the end of this article.First published online: 18 Oct 2010